ANALISIS PERILAKU MANAJEMEN KEUANGAN PADA IBU RUMAH TANGGA DESA CISAAT KECAMATAN WALED KABUPATEN CIREBON - Anggi Pebriyanti (2020)
This study uses quantitative research, aims to determine the effect of financial literacy, income, and financial attitudes on financial management behavior in housewives in Cisaat Village, Waled District, Cirebon Regency. The population used in this study is the Housewife of Cisaat Village, Waled District, Cirebon Regency. The sample size taken in this study was 75 respondents, using probability sampling methods especially simple random sampling. Data collection uses random questionnaire distribution to housewives in Cisaat Village. Data analysis technique used PLS (Partial Least Square) analysis with smartPLS version 3.0. The results showed that (1) financial literacy has an effect on financial management behavior, (2) income has no effect on financial management behavior, (3) financial attitude has no effect on financial management behavior.